2015
DOI: 10.1155/2015/352979
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Transcranial Radiation for Major Depressive Disorder: Proof of Concept Study

Abstract: Transcranial near-infrared radiation (NIR) is an innovative treatment for major depressive disorder (MDD), but clinical evidence for its efficacy is limited. Our objective was to investigate the tolerability and efficacy of NIR in patients with MDD. We conducted a proof of concept, prospective, double-blind, randomized study of 6 sessions of NIR versus sham treatment for patients with MDD, using a crossover design. Four patients with MDD with mean age 47 ± 14 (SD) years (1 woman and 3 men) were exposed to irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
91
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 23 publications
(31 reference statements)
2
91
2
1
Order By: Relevance
“…In agreement with other reports (Bettio, et al, 2014; Freitas et al, 2014), five days of sub-chronic restraint stress in our study resulted in an increase in the immobility time as compared to the control animals. Recently, transcranial NIR PBM therapy has been suggested as a non-invasive neurostimulation modality in the central nervous system and is emerging as a novel promising treatment to defeat depression (Caldieraro et al, 2018; Cassano et al, 2015; Cassano et al, 2016; Salehpour and Rasta, 2017). Previous reports from our laboratory and others have shown that repeated delivery of NIR laser therapy produces an antidepressant-like effect in the FST (Mohammed, 2016; Salehpour et al, 2016; Wu et al, 2012; Xu, et al, 2017) and TST (Xu, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with other reports (Bettio, et al, 2014; Freitas et al, 2014), five days of sub-chronic restraint stress in our study resulted in an increase in the immobility time as compared to the control animals. Recently, transcranial NIR PBM therapy has been suggested as a non-invasive neurostimulation modality in the central nervous system and is emerging as a novel promising treatment to defeat depression (Caldieraro et al, 2018; Cassano et al, 2015; Cassano et al, 2016; Salehpour and Rasta, 2017). Previous reports from our laboratory and others have shown that repeated delivery of NIR laser therapy produces an antidepressant-like effect in the FST (Mohammed, 2016; Salehpour et al, 2016; Wu et al, 2012; Xu, et al, 2017) and TST (Xu, et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…25,26,[44][45][46] Although PBM has been around since the 1960s 47,48 (originally called "low-level laser therapy" 49 ), it has only recently been applied in different populations as a neuropsychological intervention for enhancing brain function. 25,26,[44][45][46] Although PBM has been around since the 1960s 47,48 (originally called "low-level laser therapy" 49 ), it has only recently been applied in different populations as a neuropsychological intervention for enhancing brain function.…”
Section: Photobiomodulation (Pbm) Is a Newly Developed Noninvasivementioning
confidence: 99%
“…25,26,[44][45][46] Although PBM has been around since the 1960s 47,48 (originally called "low-level laser therapy" 49 ), it has only recently been applied in different populations as a neuropsychological intervention for enhancing brain function. 45 26 In addition, the remission of symptoms of patients with major depression and anxiety was observed following PBM.…”
Section: Photobiomodulation (Pbm) Is a Newly Developed Noninvasivementioning
confidence: 99%
“…It was found that, after two weeks, the mean Hamilton Depression Rating Scale (HDRS) score for the group had decreased by about 10 points (23.9 +/−8.8 SD to 13.2) and 60% had achieved remission, although by the four week mark symptoms had begun to reappear [100]. Additionally, Cassano et al [101] studied the effects of multiple PBM treatments administered over three weeks, and compared these results to those of three weeks of sham treatment, with a double-blind status being maintained for the duration of the seven week period (a washout week was designated between the two three week treatment periods). The light parameters utilized were 808nm wavelength, 700 mW/cm 2 irradiance, and 84 J/cm 2 fluence (see figure 7).…”
Section: Depression and Other Psychiatric Disordersmentioning
confidence: 99%